Evidence-Based User Interface Sanitation Technology Selection for Urban Slums: A Multi-Criteria Analysis; The Case of Jimma Town, Ethiopia - Dereje Oljira Donacho; Gudina Terefe Tucho; Wuhib Zeine Ousman; Thanyang Koang Both; Abebe Beyene Hailu (SAGE Publishing, 2022)
Slums are urban areas with insufficient public services and access to sanitation. Evidence-based selection of sustainable sanitation options is critical for addressing the sanitation crisis in slums. This mixed methods study was conducted in Jimma Town, southwest Ethiopia, to assess sanitation status and prioritize sustainable sanitation options for slums. The study was done in 2 phases: quantitative and qualitative. The quantitative cross-sectional household survey aimed to assess sanitation status and the qualitative exploratory method to explore alternative sanitation options and prioritize sustainable alternatives. A total of 310 households were chosen using systematic random sampling methods, of which 302 participated. Data was gathered through interviews, which were supplemented with questionnaires and observation checklists, and 2 focus group discussions (FGD) were held. First, FGD was with expertise in the sanitation sector, and the second was with community members. The state of sanitation was summarized, and multi-criteria analysis (MCA) was used to prioritize sustainable sanitation options. According to our findings, 68% of households had access to improved facilities, and 22.5% didn't have any form of toilet facility. About 7 off-site and on-site user interface sanitation technology options were considered in the selection of alternative sanitation technologies, and each option was evaluated against 17 health, economic, social, technical, and environmental criteria. In the final analysis, the options with the highest scores for the setting were flush to septic tanks, compost toilets, and biogas toilets. Mobilizing such a promising sanitation option is recommended for future interventions.